From the kingdom of memory reminiscences - Wiesel, Elie 1928-2016 (Summit Books, 1990)
A collection of speeches and personal essays by the humanitarian who won the Nobel Peace Prize.
Keywords: Wiesel, Elie <1928->; Wiesel, Elie -- 1928-2016; Geschichte 1900-2000; Civilization, Modern -- 20th century; Holocaust, Jewish (1939-1945) -- Influence; Jewish meditations; Autobiografie; Menschenrecht; Zivilisation; Aufsatzsammlung